Supply Chain Optimization on Company Performance in Indonesia’s Free Trade Zone, Batam City - Cecilia, Tasya; Zai, Immanuel (Penerbit Goodwood, 2026)
Purpose: This study analyzes the influence of four key elements of supply chain management inventory, supplier relationships, delivery, and information technology on operational performance and firm performance among supplier companies in Indonesia’s free trade zone, specifically Batam City. The research examines how internal resources contribute to efficiency, competitiveness, and overall business outcomes. Methodology/approach: A quantitative approach was employed through questionnaires distributed to 253 respondents from supplier companies in Batam City. Purposive sampling was used based on criteria related to supply chain activities. Data were analyzed using SmartPLS. Results/findings: The findings show that inventory, supplier relationships, delivery, and IT each have a positive and significant effect on operational and firm performance, with inventory management showing the strongest influence. Operational performance also positively affects firm performance, emphasizing the role of efficiency and reliability in achieving competitive advantage. Conclutions: Effective inventory control, strong supplier collaboration, reliable delivery, and IT utilization significantly improve company performance, supporting operational efficiency, sustainability, and the strategic value of digital and integrated supply chain management. Limitations: This study is limited to the free trade zone in Batam City and relies on self-reported data, which may introduce response bias. External factors such as policy, market conditions, and macroeconomic influences were not included. Contribution: This research provides empirical evidence on the role of supply chain resources in enhancing performance and offers insights for managers and policymakers, reinforcing RBV theory in developing regions like Batam.